Different Approaches to Modulation of Microglia Phenotypes After Spinal Cord Injury - Akhmetzyanova, Elvira; Kletenkov, Konstantin; Mukhamedshina, Yana; Rizvanov, Albert (Frontiers in Systems Neuroscience, 2019)
Microglial cells which are highly plastic immediately respond to any change in the microenvironment by becoming activated and shifting the phenotype towards neurotoxicity and/or neuroprotection. The polarization of microglia/macrophages after SCI seems to be a dynamic process and can change depending upon the microenvironment, stage, course and severity of a post-traumatic process. To date, effective methods to modulate microglia towards a neuroprotective phenotype in order to stimulate neuroregeneration are actively sought for. In this context, available approaches that can selectively impact the polarization of microglia/macrophages, regulate their synthesis of trophic factors and cytokines/chemokines, their phagocytic function and effects on the course and outcome of SCI are discussed in this review.